2018
DOI: 10.12659/msm.911178
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects the Akt Activator SC79 in Hepatic Ischemia-Reperfusion Injury

Abstract: BackgroundSC79 has been reported to protect against experimental ischemia-elicited neuronal death and brain injury and to protect myocardiocytes from hypoxia/reoxygenation (H/R) injury. Here, we investigated the effects of SC79 in primary hepatocytes in vitro and in rat liver in vivo following hypoxia-reoxygenation (H/R) and hepatic I/R injury.Material/MethodsThe livers of Sprague-Dawley rats were subjected to 45 min of ischemia followed by 2–24 h of reperfusion. The primary hepatocytes were subjected to hypox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Finally, PI3K and their downstream target Akt are family of signal transduction enzymes incorporated in regulation of cellular activation, inflammation, and apoptosis. It has been reported that PI3K/Akt/mTOR signal is involved in the process of liver IR injury (Covington et al, ; Liu et al, ; Zhou et al, ). In accordance with these previous studies, we reported a decrease in protein expression of PI3K, Akt, and mTOR in hepatic IR group as compared with sham control group.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, PI3K and their downstream target Akt are family of signal transduction enzymes incorporated in regulation of cellular activation, inflammation, and apoptosis. It has been reported that PI3K/Akt/mTOR signal is involved in the process of liver IR injury (Covington et al, ; Liu et al, ; Zhou et al, ). In accordance with these previous studies, we reported a decrease in protein expression of PI3K, Akt, and mTOR in hepatic IR group as compared with sham control group.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a great demand for Akt activators for various therapeutic applications, efforts to identify the true Akt activators were not successful until recently when a smallmolecule SC79 was discovered to be a selective, potent, and cell-permeable Akt activator, which enables cytosolic activation of Akt that recapitulates the primary function of Akt signaling (21). The cytoprotective effects afforded by SC79 have been observed in various experimental settings (8,21,59,61) For example, SC79 shielded neurons from ischemia-elicited cell death (21), protected against early brain injury following subarachnoid hemorrhage (59), protected retinal pigment epithelium cells from UV radiation (8), and provided protective effects on the hepatic I/R injury (61). We have recently shown that SC79 prevented lethal hepatic failure induced by Fas-mediated apoptosis of hepatocytes (31).…”
Section: G392mentioning
confidence: 99%
“…SC 79-mediated Akt activation rescues ischemia-induced neuronal death in rodents [165,166]. It also protects rodents from bacterial lipopolysaccharide-induced liver injury [167,168] and hepatic [169], renal [170] and cerebral ischemia [166]. Determining effects of SC 79 in metabolic diseases, either alone or in combination with IP6K inhibitor of AMPK activator will be of interest.…”
Section: Bone Marrow Stem Cellsmentioning
confidence: 99%